The Effectiveness of Islamic Group Guidance in Developing the Religious Values of BKPI IAIN Kudus Students - Arina Fithriyana (Al Hikmah: Journal of Education, 2023)
The development of technology and globalization has contributed to a decline in students’ internalization of religious values, including students of the Islamic Educational Guidance and Counseling Program (BKPI) at IAIN Kudus, who are prepared to become counselors grounded in Islamic values. This condition necessitates the provision of personal development services capable of comprehensively internalizing religious values. This study aims to examine the effectiveness of Islamic group guidance in developing the religious values of BKPI students. The study employed a quantitative approach using a pre-experimental one-group pretest–posttest design. The research subjects consisted of six students selected through purposive sampling based on low levels of religiosity. Data were collected using a Likert-scale questionnaire and analyzed using the Wilcoxon Signed Rank Test. The pretest results showed an average score of 69, while the posttest average score increased to 125.8. This indicates a significant increase of 56.8 points in students’ religious values after participating in Islamic group guidance services. These findings demonstrate that Islamic group guidance is effective as a strategy for strengthening students’ religious character in Islamic higher education institutions.